Micro Structure And Low Steel Carbon Recovery After Machining With Annealing Heat Treatment - Lerian H S M S (International Conference on Engineering and Technology Development (ICETD), 2017)
test aims to determine the carbon steel materials were in the process of anhealing after machining job. Where this test compares the process of heat treatment is given in a metal can affect the mechanical properties of the metal. One of the heat treatment process that can be given to the metal after the machining work is the process of annealing. process Annealing is a process of heat treatment of the metal by heating the metal at a certain temperature, holding at temperature and cooling the last few moments earlier metal with a very slow cooling rate. Heat treatment is given aiming to improve the mechanical properties of the metal. Air-ity it is carried out this study aimed to determine the effect inflicted on medium carbon steel after permesianan workmanship and undergo a process of annealing to violence and the resulting microstructure. This test is a testsperimental oak. Materials used are carbon steels were given the treatment machining then annealing at various temperatures 650C, 700C and 850C with holdingtime 30 minutes. Further testing hardness and microstructure observation.The results of the data analysis menujinkan average hardness of specimens without the machining process and heat treatment was 71.74 HRB and microstructure obtained Perlite + Ferrite; The average hardness values of specimens with machining process is 75.02 HRB and microstructure obtained Perlite + Ferrite + Simentit; The average hardness values of specimens with machining and heat treatment process annealing 6500C is 65.74 HRB and microstructure obtained Ferrite + Simentit; The average hardness values of specimens with machining and heat treatment process annealing 7000C is 66.02 HRB and microstructure obtained Ferrite + Simentit; The average hardness values of specimens with machining and heat treatment process annealing 8500C is 67.56 HRB and microstructure obtained Ferrite + Simentit